Nomogram individually predicts the risk for distant metastasis and prognosis value in female differentiated thyroid cancer patients: A SEER-based study - Wang, Wenlong; Shen, Cong; Yang, Zhi (Frontiers in Oncology, 2022)
Objective: Distant metastasis (DM) is an important prognostic factor in differentiated thyroid cancer (DTC) and determines the course of treatment. This study aimed to establish a predictive nomogram model that could individually estimate the risk of DM and analyze the prognosis of female DTC patients (FDTCs). Materials and Methods: A total of 26,998 FDTCs were retrospectively searched from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2018, and randomly divided into validation and training cohorts. Univariate and multivariate analyses were performed to screen for prognostic factors, and construct a prediction nomogram. The performance of the nomogram was assessed by the area under the receiver operating characteristic curve (AUC), concordance index (C-index), and a calibration curve. The overall survival (OS) and cancer-specific survival (CSS) were evaluated by Kaplan-Meier (K-M) analysis. Results: A total of 263 (0.97%) FDTCs were reported to have DM. K-M analysis showed the association of multiple organ metastases and brain involvement with lower survival rates (P <0.001) in patients. Tumor size, age at diagnosis, thyroidectomy, N1 stage, T3-4 stage, and the pathological type were independent predictive factors of DM in FDTCs (all P <0.001). Similarly, age at diagnosis, Black, DM, T3-4 stage, thyroidectomy, and lung metastasis were determined as independent prognostic factors for FDTCs (all P <0.001). Several predictive nomograms were established based on the above factors. The C-index, AUC, and calibration curves demonstrated a good performance of these nomogram models. Conclusion: Our study was successful in establishing and validating nomograms that could predict DM, as well as CSS and OS in individual patients with FDTC based on a large study cohort. These nomograms could enable surgeons to perform individualized survival evaluation and risk stratification for FDTCs.